EFFECTS OF SPONTANEOUS AND INOCULATED FERMENTATION ON THE TOTAL PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF CABERNET SAUVIGNON WINES AND FERMENTED POMACE - Zivkovic, Nikolina (Food and Feed Research, 2024)
The total phenolic content and antioxidant activity of wine and fermented pomace (FP) from Cabernet Sauvignon grapes harvested at the stage of full ripeness were evaluated by spectrophotometric analysis. Wine and pomace were obtained after prolonged maceration during spontaneous and inoculated fermentation of fully ripe grapes. Three individual vinifications were inoculated with the following commercial yeasts: BDX (Lallemand, Montréal, QC, Canada), FX10 (Laffort, Bordeaux, France) and Qa23 (Lallemand, Montréal, QC, Canada). For each vinification, maceration lasted 0, 3, 5, 7, 14 and 21 days, respectively. The total phenolic content was deter-mined spectrophotometrically using the Folin-Ciocalteu method. Two different methods were used to evaluate the antioxidant activity of the wine and pomace samples: the Ferric Reducing Activity of Plasma (FRAP) and the Trolox Equivalent Antioxidant Capacity (TEAC). The use of a winemaking process that included different maceration times and inoculation with yeasts, as well as spontaneous fermentation, significantly modulated the total phenolic content of the obtained wines and FP. This study could provide a good basis for the practical application and obtaining wines with a high content of phenolic compounds and antioxidant properties.